Reimagining salmon supply chains: a sustainability comparison of 3D-printed and traditional production - Li, Wenqi; Ekren, Banu Y.; Aktas, Emel (Elsevier, 2025)
The seafood industry faces growing sustainability challenges, including overfishing, resource inefficiency, and environmental degradation, necessitating innovative production alternatives. While traditional SCs benefit from established infrastructure and consumer trust, their high resource demand and operational inefficiencies highlight the need for sustainable alternatives. This study compares traditional and 3D-printed salmon SCs, using process mapping by flowcharting and sustainability metrics to evaluate their environmental, economic, and social impacts. Findings indicate that 3D-printed salmon reduces carbon emissions by up to 86% and freshwater consumption by 95%, primarily by eliminating farming, feed production, and long-distance cold storage. Additionally, localized production lowers logistical costs and enhances resource efficiency. Despite challenges related to consumer acceptance, regulatory approval, and scalability, 3D printing presents a promising complement to aquaculture, supporting long-term sustainability in seafood production.
Keywords: 40 Engineering; 4007 Control Engineering, Mechatronics and Robotics; 4008 Electrical Engineering; 12 Responsible Consumption and Production; 14 Life Below Water; Sustainability; 3D printing; salmon SC; process mapping by flowcharting; additive manufacturing